The Control of Non Isothermal CSTR Using Different Controller Strategies - F. Zuhwar, Zahra'a (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
In all process industries, the process variables like flow, pressure, level, concentrationand temperature are the main parameters that need to be controlled in both set pointand load changes.A control system of propylene glycol production in a non isothermal (CSTR) wasdeveloped in this work where the dynamic and control system based on basic massand energy balance were carried out.Inlet concentration and temperature are the two disturbances, while the inletvolumetric flow rate and the coolant temperature are the two manipulations. Theobjective is to maintain constant temperature and concentration within the CSTR.A dynamic model for non isothermal CSTR is described by a first order plus deadtime (FOPDT).The conventional PI and PID control were studied and the tuning of controlparameters was found by Ziegler-Nichols reaction curve tuning method to find thebest values of proportional gain (Kc), integral time ( I) and derivative time ( D).The conventional controller tuning is compared with IMC techniques in this work andit was found that the Ziegler –Nichols controller provides the best control for thedisturbance and the worst for the set-point change, while the IMC controller resultsshow satisfactory set-point responses but sluggish disturbance responses because theapproximate FOPTD model has relatively small time delay.Feedforward and feedforward combined with feedback control systems were used asanother strategy to compare with above strategies. Feedforward control provides abetter response to disturbance rejection than feedback control with a steady statedeviation (offset). Thus, a combined feedforward-feedback control system is preferredin practice where feedforward control is used to reduce the effects of measurabledisturbances, while feedback trim compensates for inaccuracies in the process model,measurement error, and unmeasured disturbances. Also the deviation (offset) infeedforward control was eliminated.